A new approach for one-dimensional sine-Gordon equation - Akgul, Ali; İnç, Mustafa; Kilicman, Adem; Baleanu, Dumitru (Springer International Publishing Ag, 2016)
In this work, we use a reproducing kernel method for investigating the sine-Gordon equation with initial and boundary conditions. Numerical experiments are studied to show the efficiency of the technique. The acquired results are compared with the exact solutions and results obtained by different methods. These results indicate that the reproducing kernel method is very effective.
Keywords: reproducing kernel method; sine-Gordon equation; bounded linear operator; homogenizing